The In Vitro Study: Anti Aeromonas hydrophila of Ethanol Extract of Kamboja Leaves (Plumeria alba) - Ikrom .; Denok Asih T.R.; Reni Wira A.; Bintang Perkasa B; Rafika Tiara N.; Wasito . (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
Motile aeromonas septicemia (MAS) caused by Aeromonas hydrophila could attack seriously freshwater fish in Indonesia. Its mortality rate was reported to be 100% on fish population. According to the Commission of Healthy Fish and National Environment, the MAS has been determined as one of major diseases in Indonesia. However, its therapy using antibiotics is still difficult because the MAS has so many different strains and can be resistant to drugs. If the antibiotics given over the maximal limit this will be able to make the fish (food products) is unsafe for human consumption. One effort to do is by using a traditional herbal medicine. Kamboja leaves is reported to contain flavonoid as antibacterial agent. Therefore, this research is aimed to determine the effectiveness of kamboja leaves extract as antibacterial agent using diffusion and dilution method in vitro. Inhibition zone of diffusion method and bacterial growth are observed by diffusion and dilution approaches, rescpectively. The results of the present study showed that 8% concentration of kamboja leaves extract was good enough to prevent bacterial growth by dilution method, whereas by diffusion method, it needs 100% of the extract concentration. The zones of growth inhibition is 1.307 cm cm which is almost the same as the diameter (1,637 cm.) achieved by using 30 µg tetracycline. The zones of bacterial growth inbihition due to the extract still persists on the day 10. But, for the antibiotic, the the zones of bacterial growth inbihition is already faded starting from the day 4. Therefore, it is concluded that kamboja leaves extact is more potent than that of antibiotic (tetracycline) in inhibiting bacterial growth in vitro.